Analisis Konten Youtube Bobon Santoso pada Episode Kuali Merah Putih dalam Membangun Semangat Nasionalisme Penonton - Yulitasari, Like Amelia; Een Irianti; Mad Yoman (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The aim of the research carried out is to find out how the meaning of denotation, connotation and myth is analyzed in Bobon Santoso's YouTube content in the Kuali Merah Putih episode so as to build the spirit of nationalism in the audience. Data collection was carried out using Roland Barthes' semiotic analysis, literature study and documentation so that in the end it created a conclusion about the meaning of the Kuali Merah Putih denotation, namely the spirit of nationalism is depicted in scenes where activities such as flag ceremonies, singing the national anthem, regional art performances become media in instilling noble values. nation and nationalism in everyday life and also in the world of elementary school children's education. The connotation meaning, Kuali Merah Putih is the stretching of the Red and White flag along the road which involves all elements of Papuan society. A narrative that makes it clear that the Red and White is still flying high in the land of Papua even though it is on the edge of Indonesia and rarely receives attention from the government. And the myth, the Red and White Cauldron, namely the spirit of nationalism, should be spread from an early age and from the tip of Aceh to Papua there without distinction between language, ethnicity and other differences.